The Strategies Hotel Effort in Improving Food and Beverage Services and Customer Satisfaction (Case Study : Angkasa Raya Hotel Kabupaten Dairi) - Edy Erianto (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
Various foods and drinks served at the restaurant at the hotel are a strategy for the services provided in order to achieve customer satisfaction who visits a hotel. Customer satisfaction is the level of a person's feelings after comparing the service received with his expectations. This study aims to determine the extent of the relationship between the services provided which is the main objective of the service company. This type of research approach used in this research is a quantitative approach, where the data sources are presented in the form of numbers. This research is focused on how the relationship between service and customer satisfaction. The results showed that there was a significant relationship between service and customer satisfaction with a probability value of 0.000. Judging from the value of the correlation coefficient (r) is 0.985. This means that an increase in service will be followed by an increase in customer satisfaction.